Germination and seedling growth of amburana cearensis (AllemÃo) A.C. smith as a function the weight of seeds and abiotic factors - JoÃo Paulo Nobre de Almeida (2014)
Given the needs of reclamation is increasing interest in the propagation of native species, which requires basic information about their germination characteristics and ecophysiological. The Amburana cearensis (AllemÃo) A.C. Smith known as cumaru is a species widely used for restoration of the landscape. The aim of this study was to investigate the germination and seedling growth of cumaru depending on the weight of the seeds under conditions of light, temperature, drought stress, as well as to determine the seed imbibition curve, internal morphology, chemical composition and quantification of the coumarin. Initially seeds were individually weighed and separated into three weight classes (light, medium and heavy), these being submitted to the determination of water content, thousand seeds weight and germination tests in two light conditions (presence and absence ) and six schemes temperatures (20, 25, 30, 35, 40, and 20-30 ÂC). In addition to these tests, it was determined the imbibition curve of each weight class and made assessment of drought stress tolerance under different potentials(-0.2, -0.4, -0.6, -0.8 and -1,0 MPa). The experiments were arranged in a completely randomized design in four replications for each treatment. For the internal morphology of seeds were used in cytochemistry usual techniques for the identification of the main structures and substances reserves. To visualize the coumarin in the seeds by NMR spectroscopy was used. The optimum conditions for seed germination occurred at 30 ÂC, which are insensitive to light and vigor seeds for light and medium. The best conditions for seedling growth occurred with the light and medium seeds at 25 and 30 ÂC and in the presence of light, with temperatures of 35 and 40 ÂC harmful. Light and medium seeds showed the same pattern of water absorption, while not reach the heavy phase III of the curve. The decrease in the water potential of the substrate affect the germination and growth of seedlings from seed medium and heavy compared to the light, and from -0.6 MPa in a condition strictly limiting seedling development. The chemical constituents present in the seeds of A. cearensis are quantitatively different depending on the weight of the seeds, and the heavy characterized by a high content of lipids. The NMR spectroscopy falls greater proportion of coumarin in seed extract heavy and medium, possibly affecting ecophysiological needs of the species A. cearensis.